Silver Nanoparticles as a Novel Therapeutic Approach for Bovine Mastitis: Efficacy and Comparative Analysis an Antimicrobial Perspective - Khan, Bilal Ahmed; Javed, M Tariq; Chemma, Imtiaz; Qaisrani, Sajid Ali; Bugti, Muhammad Arif; Bilal, Muhammad; Mudassar, Muhammad; Abdullah, Obaid Muhammad; Hanif, Maryam; Ujjan, Nisar Ahmed (Indus Journal of Bioscience Research, 2025)
Mastitis is one of the most prevalent and economically important diseases that affects dairy cattle globally. The disease leads to reduced milk production, poor animal health, and increased culling rates. Bacteria are the main cause of mastitis in dairy industry, where extensive antibiotic use has contributed to the emergence of antimicrobial resistance (AMR). To address this significant challenge, antimicrobial nanoparticles have emerged as promising alternative therapy. This study evaluates the efficacy of silver nanoparticles (AgNPs) in the treatment of bovine mastitis. A total of 40 lactating cattle diagnosed with mastitis were randomly divided into two groups (n=20). One of the groups received the treatment of intramammary administration of silver nanoparticles (100 µg) combined with gentamicin (60 mg) for five consecutive days, while the control group remained untreated. The Udder milk samples were collected before and after treatment to assess somatic cell count (SCC), bacterial load, pH, specific gravity, electrical conductivity, and malondialdehyde (MDA) concentration. The Results demonstrated a significant reduction in SCC and bacterial load in the nanoparticle-treated group compared to the controlled one. Additionally, improved milk quality parameters and reduced oxidative stress markers were observed. These findings indicate that silver nanoparticles exhibit potent antimicrobial properties and could serve as an effective therapeutic alternative for managing mastitis while mitigating the risk of AMR. Further studies are warranted to explore their long-term efficacy and safety in dairy herds.